Selective Targeting of 4SO4-N-Acetyl-Galactosamine Functionalized Mycobacterium tuberculosis Protein Loaded Chitosan Nanoparticle to Macrophages: Correlation With Activation of Immune System - Mubin, Nida; Umar, Mohd. Saad; Zubair, Swaleha; Owais, Mohammad (Frontiers in Microbiology, 2018)
In the present study, we investigated potential of chitosan-based nanoparticles (CNPs) to deliver loaded therapeutic molecules to pathogen harbouring macrophages. We fabricated stable CNPs by ionic cross linking method and evaluated their potential to target RAW 264.7 cells. The physicochemical characterization of as-synthesised CNPs was determined using electron microscopy, infrared microscopy and zeta potential measurement. Next, cellular uptake and Intracellular localization studies of CNPs were followed in living RAW 264.7 cells using confocal microscopy. We found that both Acr-1 loaded chitosan nanoparticle (CNP-A) and 4-SO4-GalNAc ligand harbouring (CNP-L) experience increased cellular uptake by M. smegmatis infected RAW cells. Following cellular digestion in model macrophages (RAW) CNPs provide an increased immune response. Further, 4-SO4-GalNAc bearing CNP-L exhibits high binding affinity as well as antibacterial efficacy towards M.smegmatis. The data of the present study suggest that CNP based nanoparticle offer a promis¬ing delivery strategy to target infected macrophages for prevention and eradication of intracellular pathogens such as M. smegmatis.